Geotourism Potential on Geosites in Natuna Geopark - Pratiwi, Prisca Nurul; Rosana, Mega Fatimah; Arfiansyah, Kurnia (Journal of Geological Sciences and Applied Geology, 2021)
Natuna is a district located in the Riau Islands Province. The Natuna area, consist of several islands. The main island namely Bunguran island, where the capital city of Natuna Regency is located. The islands have several rare geological heritages that has national and international significant value. The islands also have been designated as Natuna National Geopark since 2018. The purpose of this study is to analyze the potential of geotourism in several geological site of the Natuna Geopark. The research method used is collection and data analysis from secondary data that available, The geotourism components category are used classification by Newsome & Dowling (2010). Some geological diversities are used as geosites that has potential to be development as geotourism area. The results show that several geological sites in the Natuna Geopark can be developed and used as geotourism activities including: geosite for sightseeing; geo-sports; geo-study; geo-conservation and geo-education; and geo-festival. There are 11 geosites that have the potential to develop geotourism components, including Bukit Gundul, Gunung Ranai, Tanjung Senubing, Tanjung Datuk, Pantai dan Gua Kamak, Gugus Pulau Tiga, Pulau Senoa, Bukit Kapur, Pulau Akar, Pusat Informasi Geologi, and Batu Rusia. Some of the sites are already facilitated with infrastructure for tourism.Keywords: Geotourism, Geosite, Geological Heritage, Natuna Geopark.